PENGARUH PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM’S ACHIEVEMENT DIVISION (STAD) TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN SEJARAH DI SEKOLAH MENENGAH ATAS NEGERI (SMAN) 1 ROKAN IV KOTO KABUPATEN ROKAN HULU. - Samja, Joni; ', Prof. Dr. Isjoni, M.Si; ', Asril, M.Pd (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrakc: This research is motivated by the lack of student learning outcomes in subjects History Education at SMA Negeri 1 Rokan IV Koto, especially in class XI Social Sciences. The research aimed to determine whether there is significant influence between the use of cooperative learning model's Student Team Achievement Division (STAD) to the learning outcomes of students at SMA Negeri 1 Rokan IV Koto. This research is a Quasi experiment, which researchers act directly as a teacher in the learning process. The population in this study were all students of State Senior High School 1 Rokan IV Koto totaling 112 students. While the authors take a sample class is class XI XI Social Sciences as a class one and class XI Experimental Social Sciences two as control classes, and to take samples of the writer using purposive sampling technique. That is one of the techniques of sampling research conducted by the author with the deliberate taking samples and the presence of certain considerations. And for retrieval of data in this study using observation, testing and documentation. Based on analysis of these data, conclude that the results of student learning using cooperative learning model's Student Team Achievement Division (STAD) is better than using learning lecture. It is evident from the high student learning outcomes that are in the experimental class than in the control class. It can be concluded that there are significant differences between students who use cooperative learning model Student Team's Achievement Division (STAD) with students using instructional lectures on educational subjects History class XI School SMA Negeri 1 Rokan IV Koto District of Rokan IV Koto Rokan Hulu.Key Words: Team's Student Achievement Division, Learning Outcomes